Early years study : reversing the real brain drain (final report) - McCain, Margaret Norrie; Mustard, J. Fraser; Canadian Institute for Advanced Research (Toronto : Canadian Institute for Advanced Research, 1999)
This Report lays out the major reasons for our argument that the time is now for a major effort by all parts of society to improve the opportunities for optimal early child development and parenting for all families in Ontario.
Includes bibliographical references.
Keywords: Early childhood education -- Government policy -- Ontario; Early childhood education -- Parents participation -- Ontario; Preschool children -- Services for -- Ontario; Family services; Family policy; Child care services; Children; Child development; Economic development